Antioxidant and Total Phenolic Testing of Ethanolic Extract of Lime and Kaffir Lime Peel Waste and Peel Off Mask Formulation - Laili Nailul Muna; Erna Wulandari; Farhatul Uyun; Enny Riyan Hasni (Universitas Muhammadiyah Surakarta, 2025)
The use of synthetic ingredients in cosmetics causes many side effects such as premature aging, skin irritation, acne, blackheads and so on. So it is necessary to develop cosmetics from natural ingredients, such as using citrus waste to make peel-off masks. Development of peel-off mask preparations using active ingredients from kaffir lime peel and lime peel waste which have antioxidant activity and total phenolic content. The preparation of peel-off masks from citrus peel waste was carried out by extracting phenolic compounds from citrus peels using the maceration method with ethanol solvent and continued by formulating peel-off mask preparations with PVP and PVA bases. Furthermore, the peel off mask preparation was tested which included organoleptical, pH, adhesion, spreadability and viscosity tests. The method used to analyze the total phenolic content using Folin Ciocalteau method, while the antioxidant activity analysis was tested with DPPH method. The results of this study showed that the measurement of total phenolic content by Folin Ciocalteau method resulted in a value of 862.05 µg/ml per 1000µg of extract, while the measurement of antioxidant activity by DPPH method using a spectrophotometer at a wavelength of 515.5 nm amounted to 63.13 µg/ml with a positive control of vitamin C of 50.17 µg/ml. The peel off mask developed has good physical properties with the value of the preparation obtained pH 6, the value of spreadability 10.35 ± 0.41 grams.cm/s, the value of stickiness 8.00 ± 0.00 seconds, the value of viscosity 2,110.07 ± 83.97 cPa.